Leśmian romantyczny: Rec. Piotr Szwed, /Oddaleniec/ Poezja Bolesława Leśmiana wobec romantyzmu polskiego, Wydawnictwo Naukowe „Śląsk", Katowice 2014, ss.296 - Trybuś, Krzysztof (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
The author of the review discusses in detail six chapters of Piotr Szwed's book /Oddaleniec/ Poezja Bolesława Leśmiana wobec romantyzmu polskiego. He focuses on the eponymous link between Bolesław Leśmian and the the legacy of Polish Romanticism. Also analyzed are Leśmian's references to works by poets such as Adam Mickiewicz and Juliusz Słowacki. The quality of the reviewed study and its position within the existing research have been highly appraised.